Inheritance studies for stripe rust and identification of multiple rust resistantgenotypes in bread wheat (Triticum aestivum) - KUMAR, VISHNU; SHEKHAWAT, P S; KUMAR, SUDHEER; GANGWAR, O P; TYAGI, B S; GUPTA, ARUN; GUPTA, VIKAS; SINGH, G P (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during winter (rabi) season 2021–22 at ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana to ascertain genetic basis of stripe rust (YR) resistance with bread wheat (Triticum aestivum L.) resistant stock, IC0640204 and considering seven susceptible genotypes, namely IC261932, IC532880, IC536321, EC609338, Restorer5, Restorer37 and Restorer38 for YR, summer nursery 2022 and 2022–23. IC0640204 conferred YR resistance against 10 pathotypes at the seedling stage, including the prevalent YR races, 110S119 and 238S119. Seven highly susceptible bread wheat genotypes were crossed with IC0640204 during winter (rabi), 2021–22 at Karnal and the developed materials were advanced at Dalang Maidan, Himachal Pradesh. During rabi 2022–23, the monogenic dominant inheritance (3R:1S) was observed in the F2 generation at both Karnal and Durgapura locations, indicating presence of a major gene in the genotype IC0640204. Furthermore, agronomically promising genotypes were screened at eight locations each against stripe, leaf and stem rusts under artificial epiphytotic conditions to identify multiple rust resistant genotypes. The genotypes WAP2206, WAP2207 and WAP2208 conferred seedling resistance (0) against the most virulent YR pathotypes, 110S119 and 238S119. The genotype WAP2206 showed resistance against stem (ACI:0.7) and brown rusts (ACI:0.3), while WAP2207 conferred resistance against stripe (ACI:0.6) and leaf rusts (ACI:0.3). The widely grown wheat cultivars such as HD2967, HD3086 and DBW187 have been compromised against these newly evolved YR races. Therefore, IC0640204 has great significance for delivering resistance into the breeding programs. Several deployed genes for leaf and stem rust namely, Lr9, Lr19, Lr26, Lr28 and Sr24 and Sr25 have been overcome by the virulent pathotypes. The genotypes, WAP2206, WAP2207, WAP2211 and WAP2212 can be deployed for pre-emptive breeding and enriching allelic diversity.